1993
DOI: 10.1128/jb.175.3.750-757.1993
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide synthesis in relation to nodulation behavior of Rhizobium leguminosarum

Abstract: In this study, we characterized four Tn5 mutants derived from Rhizobium leguminosarum RBL5515 with respect to synthesis and secretion of cellulose fibrils, extracellular polysaccharides (EPS), capsular polysaccharides, and cyclic beta-(1,2)-glucans. One mutant, strain RBL5515 exo-344::Tn5, synthesizes residual amounts of EPS, the repeating unit of which lacks the terminal galactose molecule and the substituents attached to it. On basis of the polysaccharide production pattern of strain RBL5515 exo-344::Tn5, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 37 publications
0
43
0
1
Order By: Relevance
“…Until the early stationary phase of a culture of wild-type bacteria, a neutral glucan consisting of 100% glucose and an acidic polysaccharide whose carbohydrate composition closely resembles that of EPS are both present in the CPS fraction. The neutral glucan may be a cyclic ␤-1,2-glucan, as previously identified for different Rhizobium species (12), and its secretion has been reported to be enhanced in cultures of EPS-deficient rhizobia (11). As judged from the data obtained from NMR studies and methylation analysis of the acidic CPS, we concluded that CPS is similar if not identical to EPS (Fig.…”
Section: Discussionmentioning
confidence: 55%
“…Until the early stationary phase of a culture of wild-type bacteria, a neutral glucan consisting of 100% glucose and an acidic polysaccharide whose carbohydrate composition closely resembles that of EPS are both present in the CPS fraction. The neutral glucan may be a cyclic ␤-1,2-glucan, as previously identified for different Rhizobium species (12), and its secretion has been reported to be enhanced in cultures of EPS-deficient rhizobia (11). As judged from the data obtained from NMR studies and methylation analysis of the acidic CPS, we concluded that CPS is similar if not identical to EPS (Fig.…”
Section: Discussionmentioning
confidence: 55%
“…(6) have recently characterized a mutant of Rhizobium leguminosarum that lacks the terminal sugar of the exopolysaccharide and also produces very little exopolysaccharide.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Xanthomonas campestris, it has been shown that mutants that are blocked in the transfer of the fourth or fifth sugar to the lipid-linked subunit can produce altered forms of xanthan gum consisting of a three-or four-sugar repeat unit, respectively, L-Glc 3-1,4 Glc -1,4 Glc P-13 Gal3 P1,. 6 61 n acetyl Glc I3- 1,6 Glc I3- 1,3 Glc6 succinyl (-) |3- 1,3 GIc4, pyruvyl (-) (1, 52).…”
mentioning
confidence: 99%
“…The Rlt RBL5515 strain carrying mutation in the pssJ gene (known as exo344::Tn5), synthesizes residual amounts of EPS, the repeating unit of which lacks the terminal galactose of the side chain. On the basis of the structural features of the polysaccharides synthesized and the results of an analysis of the enzyme activities involved, it was hypothesized that the galactosyltransferase catalyzing formation of the 1-3 linkage between sub-terminal (Glc) and terminal (Gal) sugar residues in the octasaccharide unit is affected in this strain [6]. PssJ did not reveal any homologs in protein databases and therefore it could be referred to a family of "not-classified glycosyltransferases" (CAZy database).…”
Section: Assembly Of the Eps Repeating Unitmentioning
confidence: 99%
“…Glucomannan was shown to be important for lectin-mediated polar attachment to Vicia sativa and Pisum sativum root hairs and competitive nodulation [4,5]. The CPS is tightly associated with the cell surface of bacteria forming a polysaccharide matrix surrounding the bacteria [6]. Differences in noncarbohydrate substitutions, such as O-acetyl, pyruvate, and 3-hydroxybutyrate, may distinguish anionic capsule-bound polysaccharides from secreted EPS.…”
Section: Introductionmentioning
confidence: 99%